Covid-19 in children: A brief overview after three months experience. (September 2020) - De Luca, Carmen Dolores; Esposito, Emanuele; Cristiani, Luca; Mancino, Enrica; Nenna, Raffaella; Cortis, Elisabetta; Midulla, Fabio
Abstract: Severe Acute Respiratory Syndrome – Coronavirus – 2 (SARS-CoV-2) and its related Coronavirus Disease – 19 (COVID-19) has become a health emergency worldwide. The medical community has been concerned since the beginning of the outbreak about the potential impact of COVID-19 in children, especially in those with underlying chronic diseases. Fortunately, COVID-19 has been reported to be less severe in children than in adults. However, epidemiologic and clinical data are scarce. Children show unique features of SARS-CoV-2 involvement that may account for the low rate of infection and death in this age group. The purpose of this review is to summarize the most relevant evidence of COVID-19 in children highlighting similarities and differences with adults.